2017
DOI: 10.14202/vetworld.2017.979-983
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity of yeasts against some pathogenic bacteria

Abstract: Aim:This study was designed to isolate and identify yeast species from milk and meat products, and to test their antimicrobial activity against some bacterial species.Materials and Methods:A total of 160 milk and meat products samples were collected from random sellers and super markets in New Damietta city, Damietta, Egypt. Samples were subjected to yeast isolation procedures and tested for its antimicrobial activity against Staphylococcus aureus, Pseudomonas aeruginosa, and Escherichia coli. In addition, all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
30
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 24 publications
4
30
0
1
Order By: Relevance
“…Given that we recently demonstrated that S. cerevisiae CNCM I-3856 (GI) is unable to co-aggregate with G. vaginalis [ 49 ], it is possible that S. cerevisiae CNCM I-3856 inhibition of G. vaginalis biofilm formation can be ascribed to biological instead of mechanical effects. Indeed, previous studies demonstrated that members of the Saccharomyces genus can produce extracellular protease and other compounds able to inhibit the growth of many pathogenic bacterial species [ 82 , 83 ]. In addition, given that the presence of the sialidase gene is associated with G. vaginalis biofilm formation [ 84 ], the capacity of S. cerevisiae CNCM I-3856 in inhibiting sialidase activity [ 49 ] could account for the observed effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that we recently demonstrated that S. cerevisiae CNCM I-3856 (GI) is unable to co-aggregate with G. vaginalis [ 49 ], it is possible that S. cerevisiae CNCM I-3856 inhibition of G. vaginalis biofilm formation can be ascribed to biological instead of mechanical effects. Indeed, previous studies demonstrated that members of the Saccharomyces genus can produce extracellular protease and other compounds able to inhibit the growth of many pathogenic bacterial species [ 82 , 83 ]. In addition, given that the presence of the sialidase gene is associated with G. vaginalis biofilm formation [ 84 ], the capacity of S. cerevisiae CNCM I-3856 in inhibiting sialidase activity [ 49 ] could account for the observed effect.…”
Section: Discussionmentioning
confidence: 99%
“…First, S. cerevisiae CNCM I-3856 can degrade the extracellular matrix by secreting enzymes [ 82 ] such as amylase, protease, and lipase that favor penetration of the yeast into the biofilm, allowing it to displace G. vaginalis from the abiotic surface. Second, the probiotic can have an antimicrobial activity by secreting specific compounds [ 82 , 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…The chloroform extract showed higher antimicrobial activity as compared to the ethyl acetate extract which may be attributed to the more number of bioactive chemical constituents in the chloroform extract as compared to the ethyl acetate extract evaluated by GC-MS analysis. Several research studies have previously reported the antimicrobial nature of yeasts especially in biopreservation of food and yeasts as biocontrol agents (Younis et al, 2017; Mewa-Ngongang et al, 2017; Knight and Witzgall, 2013) but the antimicrobial nature of yeasts in light of its chemical constituents has not been given much importance. Thus this study reports the probability of antimicrobial nature of the yeast isolated from insect gut with regards to its bioactive chemical constituents.…”
Section: Discussion:-mentioning
confidence: 99%
“…Then, with the achievement of new findings on probiotics and how they work, scientists began to use these beneficial bacteria to improve the growth performance of animals [13]. Probiotics have several benefits including efficient adherence to the intestinal epithelial cells to reduce or prevent the colonization of pathogens [12,14], competitive growth with pathogens [3], and also the production of metabolites to inhibit or kill pathogens [15,16]. Probiotics, defined as “live microorganisms which, when administered in adequate amounts, confer a health benefit on the host”, constitute a potential tool in the reduction of mortality in the rearing of aquatic organisms [12].…”
Section: Introductionmentioning
confidence: 99%